Relay-aided interference alignment - Teo, Zenn (2019)
Interference is inherent in any multi-user wireless system. In this system, the wanted signal will be transmitted and detected while hearing unwanted signals from other users, this phenomenon is known as interference. As a result, the throughput for each end-user fluctuates dramatically with every new user entering and this could potentially cause disruption. Therefore, there is a need to study the effects of interference and possible solutions to improve the situation in a Multiple-In-Multiple-Out (MIMO) system. This paper will show the effects of interference through the use of Bit Error Rate (BER) studies and also various potential methods such as the Zero Forcing (ZF) equalizer and Minimum Mean Square Error (MMSE) that could help improve the system.